Changes in the relationship between Hungarian Grey cows (Bos primigenius taurus hungaricus) and their calves in the period from calving to four months of age - Lenner, Ádám; Ragán, Péter; Komlósi, István (Acta Agraria Debreceniensis, 2022)
The ability of cows to care for their offsprings is a very important trait concerning beef cattle. Maternal instincts are highly influenced by breed, specific cow, and social and rearing environment. In 2020, at the Szamárháti farm of the Tiszatáj Public Foundation, we selected 15 dam-calf pairs and studied them for four months from the birth of the calves. We grouped calf-rearing behaviors according to strength and analyzed the related changes during the program. At the beginning of the relationship, "standing close to each other" (53%) and "suckling" (24%) characterized the pairs. After the first month, "standing or lying separated" grew by 69%, and "vocalization" by both animals fell by 66%. Even though the daily frequency of suckling decreased by 34% as the calves grew older, it remained a typical element of the relationship. Over time, the bond between the animals gradually weakened. This natural process of separation takes a month to complete.